JavaScript for Beginners Learn with 6 Main Projects - Taulien, Kalob (Packt Publishing, 2020)
Learn modern JavaScript and its fundamentals from scratch About This Video Become a confident JavaScript developer by learning how to read, write, and code in JavaScript Develop a solid understanding of JavaScript fundamentals Create dynamic web pages and projects using JavaScript In Detail This course will guide you on your journey to becoming a confident JavaScript developer by equipping you with the right techniques and knowledge of essential concepts. You will learn how to write JavaScript, along with understanding its application and how to execute it. Progressing through the sections, you'll work with the JavaScript syntax and also discover ways to easily debug JavaScript code. One of the main reasons why JavaScript is so popular is because of its ability to interact with a web page. In this course, you will learn how to accept user input, change how a page looks, and take action based on the user's action. Specific videos will also teach you about the different data types and how to use them. In addition to this, you'll delve into numbers, strings, floats, functions, undefined, and null, along with understanding their importance. The course also features a dedicated section for objects, classes, and object-oriented programming (OOP), along with covering concepts such as hoisting, closures, promises, and block scoping. Finally, you'll get to grips with topics such as APIs and Ajax requests. By the end of this course, you will be well-versed with modern JavaScript and have the skills you need to write effective JavaScript code.